Salah Naoura

Algorithms for the genome median under a restricted measure of rearrangement - Silva, Helmuth O.M.; Rubert, Diego P.; Araujo, Eloi; Steffen, Eckhard; Doerr, Daniel; Martinez, Fábio V. (RAIRO - Operations Research)
Ancestral reconstruction is a classic task in comparative genomics. Here, we study the genome median problem, a related computational problem which, given a set of three or more genomes, asks to find a new genome that minimizes the sum of pairwise distances between it and the given genomes. The distance stands for the amount of evolution observed at the genome level, for which we determine the minimum number of rearrangement operations necessary to transform one genome into the other. For almost all rearrangement operations the median problem is NP-hard, with the exception of the breakpoint median that can be constructed efficiently for multichromosomal circular and mixed genomes. In this work, we study the median problem under a restricted rearrangement measure called c4-distance, which is closely related to the breakpoint and the DCJ distance. We identify tight bounds and decomposers of the c4-median and develop algorithms for its construction, one exact ILP-based and three combinatorial heuristics. Subsequently, we perform experiments on simulated data sets. Our results suggest that the c4-distance is useful for the study the genome median problem, from theoretical and practical perspectives.
Keywords: Management Science and Operations Research; Computer Science Applications; Theoretical Computer Science

Sets of r-graphs that color all r-graphs - Ma, Yulai; Mattiolo, Davide; Steffen, Eckhard; Wolf, Isaak Hieronymus (arXiv:2305.08619)

Thermo‐chemo‐mechanical modelling of a curing process combined with mean‐field homogenization methods at large strains - Lenz, Peter; Mahnken, Rolf (PAMM)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

Model-driven Collaborative Design of Professional Education Programmes With Extended Online Whiteboards - Wolters, Dennis; Engels, Gregor (MODELSWARD'23)

A Non-Linear Mean-Field Debonding Model at Large Strains for the Analysis of Fibre Kinking in Ud Composites - Cheng, Chun; Song, Chunlei; Mahnken, Rolf; Yuan, Zhipeng; Yu, Liang; Ju, Xiaozhe

A thermodynamic framework for the phase‐field approach considering carbide precipitation during phase transformations - Westermann, Hendrik; Mahnken, Rolf (PAMM)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

A finite strain gradient theory for viscoplasticity by means of micromorphic regularization - Hamdoun, Ayoub; Mahnken, Rolf (PAMM)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

Ratings Meet Prices: The Dynamic Relationship of Quality Signals - Kaimann, Daniel; Spiess Bru, Clarissa Laura Maria; Frick, Bernd (Journal of Wine Economics)

Ultrafast Proton Transfer Pathways Mediated by Amphoteric Imidazole - Codescu, M.-A.; Kunze, T.; Weiß, M.; Brehm, Martin; Kornilov, O.; Sebastiani, D.; Nibbering, E. T. J. (J. Phys. Chem. Lett.)

A Force Field for Bio-Polymers in Ionic Liquids (BILFF) – Part 2: Cellulose in [EMIm][OAc] / Water Mixtures - Roos, E.; Sebastiani, D.; Brehm, Martin (Phys. Chem. Chem. Phys.)

Lactate-Based Ionic Liquids as Chiral Solvents for Cellulose - Radicke, J.; Roos, E.; Sebastiani, D.; Brehm, Martin; Kressler, J. (J. Polym. Sci.)

Definition of High-Risk Motion Patterns for Female ACL Injury Based on Football-Specific Field Data: A Wearable Sensors Plus Data Mining Approach - Di Paolo, Stefano; Nijmeijer, Eline M.; Bragonzoni, Laura; Gokeler, Alli; Benjaminse, Anne (Sensors)
The aim of the present study was to investigate if the presence of anterior cruciate ligament (ACL) injury risk factors depicted in the laboratory would reflect at-risk patterns in football-specific field data. Twenty-four female footballers (14.9 ± 0.9 year) performed unanticipated cutting maneuvers in a laboratory setting and on the football pitch during football-specific exercises (F-EX) and games (F-GAME). Knee joint moments were collected in the laboratory and grouped using hierarchical agglomerative clustering. The clusters were used to investigate the kinematics collected on field through wearable sensors. Three clusters emerged: Cluster 1 presented the lowest knee moments; Cluster 2 presented high knee extension but low knee abduction and rotation moments; Cluster 3 presented the highest knee abduction, extension, and external rotation moments. In F-EX, greater knee abduction angles were found in Cluster 2 and 3 compared to Cluster 1 (p = 0.007). Cluster 2 showed the lowest knee and hip flexion angles (p < 0.013). Cluster 3 showed the greatest hip external rotation angles (p = 0.006). In F-GAME, Cluster 3 presented the greatest knee external rotation and lowest knee flexion angles (p = 0.003). Clinically relevant differences towards ACL injury identified in the laboratory reflected at-risk patterns only in part when cutting on the field: in the field, low-risk players exhibited similar kinematic patterns as the high-risk players. Therefore, in-lab injury risk screening may lack ecological validity.
Keywords: Electrical and Electronic Engineering; Biochemistry; Instrumentation; Atomic and Molecular Physics; and Optics; Analytical Chemistry

Motor learning principles during rehabilitation after anterior cruciate ligament injury Prinzipien motorischen Lernens während der Rehabilitation nach vorderer Kreuzbandverletzung - Gokeler, Alli; Nijmeijer, E. M.; Heuvelmans, P.; Tak, I.; Ramponi, C.; Benjaminse, A. (Arthroskopie)
Keywords: Orthopedics and Sports Medicine

Brain activation and single-limb balance following anterior cruciate ligament reconstruction - Sherman, David A.; Baumeister, Jochen; Stock, Matt S.; Murray, Amanda M.; Bazett-Jones, David M.; Norte, Grant E. (Clinical Neurophysiology)
Keywords: Physiology (medical); Neurology (clinical); Neurology; Sensory Systems

Exergaming in older adults: the effects of game characteristics on brain activity and physical activity - Müller, Helen Martha; Baumeister, Jochen; Bardal, Ellen Marie; Vereijken, Beatrix; Skjæret-Maroni, Nina (Frontiers in Aging Neuroscience)
Introduction Exergames are increasingly used in rehabilitation settings for older adults to train physical and cognitive abilities. To meet the potential that exergames hold, they need to be adapted to the individual abilities of the player and their training objectives. Therefore, it is important to know whether and how game characteristics affect their playing. The aim of this study is to investigate the effect of two different kinds of exergame (step game and balance game) played at two difficulty levels on brain activity and physical activity. Methods Twenty-eight older independently living adults played two different exergames at two difficulty levels each. In addition, the same movements as during gaming (leaning sideways with feet in place and stepping sideways) were performed as reference movements. Brain activity was recorded using a 64-channel EEG system to assess brain activity, while physical activity was recorded using an accelerometer at the lower back and a heart rate sensor. Source-space analysis was applied to analyze the power spectral density in theta (4 Hz–7 Hz) and alpha-2 (10 Hz–12 Hz) frequency bands. Vector magnitude was applied to the acceleration data. Results Friedman ANOVA revealed significantly higher theta power for the exergaming conditions compared to the reference movement for both games. Alpha-2 power showed a more diverse pattern which might be attributed to task-specific conditions. Acceleration decreased significantly from the reference movement to the easy condition to the hard condition for both games. Discussion The results indicate that exergaming increases frontal theta activity irrespective of type of game or difficulty level, while physical activity decreases with increasing difficulty level. Heart rate was found to be an inappropriate measure in this population older adults. These findings contribute to understanding of how game characteristics affect physical and cognitive activity and consequently need to be taken into account when choosing appropriate games and game settings for exergame interventions.
Keywords: Cognitive Neuroscience; Aging

Creating water-in-salt-like environment using coordinating anions in non-concentrated aqueous electrolytes for efficient Zn batteries - Gomez Vazquez, Dario; Pollard, Travis P.; Mars, Julian; Yoo, Ji Mun; Steinrück, Hans-Georg; Bone, Sharon E.; Safonova, Olga V.; Toney, Michael F.; Borodin, Oleg; Lukatskaya, Maria R. (Energy & Environmental Science)
By using coordinating anions such as acetate, a water-in-salt-like coordination environment of Zn ions is achieved in relatively dilute conditions, leading to prolonged and efficient cycling of zinc metal anodes.
Keywords: Pollution; Nuclear Energy and Engineering; Renewable Energy; Sustainability and the Environment; Environmental Chemistry

The nature of dynamic local order in CH3NH3PbI3 and CH3NH3PbBr3 - Weadock, Nicholas J.; Sterling, Tyler C.; Vigil, Julian A.; Gold-Parker, Aryeh; Smith, Ian C.; Ahammed, Ballal; Krogstad, Matthew J.; Ye, Feng; Voneshen, David; Gehring, Peter M.; Rappe, Andrew M.; Steinrück, Hans-Georg; et al. (Joule)
Keywords: General Energy

Cooperative Android App Analysis - Pauck, Felix

Impulse zur Scherbe als Spur und künstlerisches Material - Langer, Svenja (Scherben. Der Katalog zur Ausstellung. Olav Schiedel im Raum für Kunst Paderborn. 20.05.-04.06.2023)
Die Überreste vom Tornado in Paderborn Was bleibt, sind die Scherben von zerbrochenen Dachziegeln. Olav Schiedel sammelt und kartiert Fragmente dieser Ziegel entlang der Tornadoschneise. Aus dem Objekt „Scherbe” wird das Material für eine künstlerische Auseinandersetzung. Die Ausstellung „Scherben“ verknüpft Archäologie mit bildender Kunst und zeigt die aktuelle Stadtgeschichte aus einer anderen, ungewohnten Perspektive.
Keywords: Ausstellung; Katalog; Tornado; Scherbe; Dachziegel; Spur; Kunst